ANALYSIS OF CHARACTER EDUCATION IMPLEMENTATION THROUGH 5 HABITS (SMILE, HANDSHAKE, GREETING, POLITENESS, AND COURTESY) IN SD NEGERI 1 KUTOSARI, KEBUMEN SUB-DISTRICT, KEBUMEN REGENCY IN ACADEMIC YEAR OF 2019/2020 - Khimatun Nafilah; Tri Saptuti Susiani; Muhamad Chamdani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
Abstract The objectives of the research were: (1) to describe the implementation of character education through 5 habits in SD Negeri 1 Kutosari, (2) to describe the implication of character values about 5 habits in SD Negeri 1 Kutosari, (3) to analyze the obstacles and solutions in implementing 5 habits in SD Negeri 1 Kutosari. The research used descriptive qualitative research. Type of data was qualitative data. The researcher described the analysis of character education implementation through 5 habits. Data collection techniques included observations, interviews, and qualitative questionnaires. The data validity technique was triangulation of source. Data analysis techniques included data reduction, data presentation, and verification. The results showed that the implementation of 5 habits and the implementation of character values at school run well while the obstacle was the students failed to implement 5 habits at home. It affected the implementation of 5 habits at school.  The solution was the teachers supervised and managed the students to implement 5 habits consistently in daily life. It concludes that the implementation of character education through 5 habits run very well with cumulative presentation 96,2% and the obstacle was handled by the teachers.